Reactionary policy of Lithuanian clericals in teaching history at general-education schools (1919-1940) - Pilkauskas , Z. (Psichologija, 1973)
History teaching is a constituent of pupils’ all-round development, of their world outlook formation at general-education schools. In class society various social strata struggle for the content of education, the teaching system, for the realization of teaching and educational goals. The clericals used to stress their neutrality, indifference to politics, and class contradictions. Consequently, they alleged that their teaching and educational goals did not reflect any political aspirations. Historical investigations of the problem help to disclose the regularities in the legitimation of clericalism in bourgeois Lithuanian school. This paper deals with the reactionary educational policy of Lithuanian clericals on several issues: legitimation of clericalism in school syllabi of history, the struggle of clericals and clerical bourgeoisie against the authors of non-clerical outlooks, for pro-Catholic textbooks and methods of history teaching. The syllabi, textbooks, literature on history and articles on methods of teaching published from 1919 to 1940 were analysed. The data received disclose a systematic and determined character of the infiltration of clericalism into schools of general education. History as a subject was used for the formation of the religious outlook and bourgeois-clerical ideology of pupils. Thus, the so-called indifference to politics in Lithuanian bourgeois schools proclaimed by the clericals was but a demagogic trick, masking political goals.